The grammar of words an introduction to linguistic morphology - Booij, G. E. (Oxford ; New York : Oxford University Press, 2007)
"This is a basic introduction to how words are formed. It shows how the component parts of words affects their grammatical function, meaning, and sound"--Provided by publisher.
Includes bibliographical references (p. [325]-338) and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2023. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Grammar, Comparative and general -- Morphology; Electronic books